A gender-specific measure of binge drinking among college students. - Wechsler, H (1995)
This study examined the relationship of volume of alcohol consumed to the occurrence of alcohol-related problems among male and female college students to develop a gender-specific measure of heavy episodic or binge drinking by college students for public health research. A self-administered survey was mailed to a national representative sample of students at 140 4-year colleges in 40 states and the District of Columbia. A total of 17,592 college students completed the survey. Women who typically drink four drinks in a row were found to have roughly the same likelihood of experiencing drinking-related problems as men who typically drink five drinks in a row. Use of the same standard for both sexes underestimates binge drinking and the negative health risks for women.